2020
DOI: 10.1007/s11292-020-09450-x
|View full text |Cite
|
Sign up to set email alerts
|

Animus toward Muslims and its association with public support for punitive counter-terrorism policies: did the Christchurch terrorist attack mitigate this association?

Abstract: We apply Unnever and Cullen's (2010) Racial Animus Model to examine support for punitive counter-terrorism policies before and after the 2019 Christchurch terrorist attack. MethodsWe utilize a natural experiment of survey data from Australians before (n=1191) and after (n=1344) the attack. Both surveys included a between-groups vignette describing a terrorist as either a right-wing or Islamic extremist. We examined if support for counter-terrorism policies differed between the two conditions and two surveys. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…The theoretical underpinnings of the racial animus model, the minority group threat hypothesis and racial typification of crime, implies that remediation efforts need to focus on eliminating the association of criminality with cultural minority groups (Weitzer & Tuch, 2005). Our results are consistent with previous work associating support for punitive sentencing with animus toward ethnic minority groups such as Blacks (Bobo & Johnson, 2004; Unnever et al, 2005), Hispanic Americans (Welch et al, 2011), Indigenous Australians (Brookman & Wiener, 2017a), New immigrants (Kornhauser, 2013) and Muslims (Williamson & Murphy, 2020). Our study extends the conceptualising and findings of Unnever and Cullen (2010a) and the replication study by Brown and Socia (2017) by examining different crime types using the punitive–rehabilitative dimensional scale.…”
Section: Discussionsupporting
confidence: 92%
“…The theoretical underpinnings of the racial animus model, the minority group threat hypothesis and racial typification of crime, implies that remediation efforts need to focus on eliminating the association of criminality with cultural minority groups (Weitzer & Tuch, 2005). Our results are consistent with previous work associating support for punitive sentencing with animus toward ethnic minority groups such as Blacks (Bobo & Johnson, 2004; Unnever et al, 2005), Hispanic Americans (Welch et al, 2011), Indigenous Australians (Brookman & Wiener, 2017a), New immigrants (Kornhauser, 2013) and Muslims (Williamson & Murphy, 2020). Our study extends the conceptualising and findings of Unnever and Cullen (2010a) and the replication study by Brown and Socia (2017) by examining different crime types using the punitive–rehabilitative dimensional scale.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that majority-group members, who perceive Muslims as a threat, as being religious and as supporting or being associated with terrorism, are more supportive of institutional WHAT MAKES A TERRORIST? 25 discrimination, anti-immigration policies or extraordinary detention practices among others (Doosje et al, 2009;Piazza, 2015;Welch, 2016;Williamson, 2019;Williamson & Murphy, 2020). Our research extends this work by comparatively testing the influence on both punitive and social policy support.…”
Section: Discussionmentioning
confidence: 59%
“…Also in the context of terrorism, showing empathy toward minority groups and their experiences WHAT MAKES A TERRORIST? 14 may be related to less support for punitive counter-terrorism policies (Williamson & Murphy, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Explosives and suicide bombings have been the primary means of terror in previous HW terror attacks, with a variation of mortality ranging from 3 to as high as 2996, injuries ranging from 49 to 6000, and a ratio of deaths/ total casualties of 8 to 51%. 17,[50][51][52][53][54][55][56][57] An important denominator of these attacks is the chaos and overwhelming pressure they create for emergency services, particularly healthcare. A high number of injuries require both a multiagency approach and availability of healthcare in several hospitals and healthcare facilities, along with local preparedness at the community level for both adult and pediatric conditions and military-like injuries.…”
Section: Medical Consequences Of Hwmentioning
confidence: 99%